Pemanfaatan Media Sosial Berbasis Youtube Dalam Pembelajaran Tematik Kelas 2 di Masa Pandemi Covid-19 - Februesty Maya Lestari; Imam Bahrozi (PEDIR: Journal of Elementary Education, 2021)
Abstract:. Thematic learning requires teachers who are broad minded, have high creativity, reliable methodological skills, high self-confidence, and the courage to package and develop material. Such demands aim that teachers are able to position themselves according to the times and the learning needs of students in the teaching and learning process. During the Covid-19 pandemic, when online learning, teachers could use various kind of social media as a medium learning. By utilizing various social media, it is hoped that teaching and learning activities will continue as usual, even though teachers and students cannot meet face to face directly. Teachers can take advantage of Youtube social media as a learning medium by creating content that contains learning according to basic competencies. The formulation of the problem in this study how to use Youtube social media in class 2 thematic learning during the pandemic, to analyse what supporting and inhibiting factors for teachers in using Youtube media in grade 2 thematic learning during the Covid-19 pandemic. This research is a qualitative research with a case study approach through observation, interviews and documentation. The results of this study indicate that teacher in utilizing Youtube in grade 2 thematic learning during the Covid-19 pandemic went through several prosesses ranging from planning to evalution. The teacher becomes a Youtuber by creating learning video content which is then shared by students via a link sent to the class WhatsApp group. Supporting factors are smooth internet access, learning motivation in students, good communication between teachers, students and pupils so that there is no miss of communication during online learning while the inhibiting factors are constrained by poor internet access, teacher limitations in the ability to use techonology, and back of student understanding because of its limitations.